2006
DOI: 10.1128/jcm.00902-06
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal-Drug Susceptibilities of Mycelial and Yeast Forms of Penicillium marneffei Isolates in Cambodia

Abstract: Penicillium marneffei infection is an important disease among human immunodeficiency virus patients inPenicillium marneffei, the only known dimorphic species in the genus Penicillium, was first isolated from an organ of a bamboo rat (Rhizomyces sinensis or Rhizomyces pruinosis) (2). Penicilliosis marneffei has been recognized with increasing frequency in Southeast Asia and Southern China (15,19,20). P. marneffei infection has become the third most common opportunistic infection in AIDS patients in Southeast As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
4
9
0
Order By: Relevance
“…MICs were within the range of values previously reported for this fungus (McGinnis et al 2000; Sar et al 2006). No significant differences of melanized and non-melanized cells in the different culture broths were observed between MICs of antifungal drugs.…”
Section: Resultssupporting
confidence: 85%
“…MICs were within the range of values previously reported for this fungus (McGinnis et al 2000; Sar et al 2006). No significant differences of melanized and non-melanized cells in the different culture broths were observed between MICs of antifungal drugs.…”
Section: Resultssupporting
confidence: 85%
“…P. marneffei infection is endemic among HIV-positive patients in many areas in Southeast Asia, including Thailand, Vietnam, Hong Kong, Southern China, Taiwan, India, and Laos [ 6 , 8 , 9 , 12 20 ]. So far, all reported cases of P. marneffei infections in AIDS patients have showed epidemiological link with the endemic areas except for one case reported in an African from Ghana who had never been to Southeast Asia [ 21 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…[28] and Sar et al [19] respectively. Some of the yeast and mycelial phases of isolates in this study also showed MIC ≥ 24µg/ml, which correlates to the results mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Internal transcribed spacer (ITS) region of the nuclear rDNA was ampli ed with PCR and detected with direct DNA sequencing to determine the species [18]. The mycelial and yeast form of T. marneffei were obtained as mentioned by Sar et al [19].…”
Section: (I) Isolatementioning
confidence: 99%